INTERRELIGIOUS DIALOGUE FOR LIVING TOGETHER IN HARMONY - Doss, Jude Nirmal (Journal of Dharma, 2019)
No one lives as an Island. For, every human being is a social being and every experience of human being is a dialogue with the reality. When man enters into dialogue, then such dialogue is not static but dynamic. It is also true with the Interreligious dialogue, which is much spoken in Indian context, and is also the need of the hour. Dialogue does not mean that one gives up the identity as a Christian. On the contrary, dialogue would mean being firm in one’s own belief, as a result, being open towards understanding others’ belief. Basing on this understanding, new proposals for the fruitful dialogue for living together in harmony are made. The focus of this paper is to show that the object of the interreligious dialogue is not aiming at the religious tolerance, au contraire, is fostering the religious friendship in order to live together in harmony.